Podcast-based lessons: a useful tool to improve university students’ descriptive oral skills - Sandoval Zapata, Marcos Marcelo (Instituto Tecnológico de Costa Rica, 2020)
This article aims to analyze the impact of using podcast-based lessons in order to improve descriptive oral skills in a cohort of Chilean tertiary education students. The participants underwent four synchronous podcasting sessions in which feedback was provided using an eight-criteria analytic rubric. At the end of the intervention, a focus group was conducted, in order to collect the participants’ perceptions on the new methodology. Their responses evidenced that this methodology was a valuable complement to their EFL classes, being pronunciation and fluency the criteria they perceived as the most benefitted.